Ensino de inteligência artificial : uma proposta de formação docente nas disciplinas STEAM - Flores, Diego (My University, 2023)
Thanks to scientific efforts, the dissemination of computational thinking has intensified technological innovations with the use of artificial intelligence, making them indispensable in our daily lives. Although present in the scientific environment, PC (computational thinking) has only recently revealed itself to be important in Education, therefore, one notices an emerging and significant concern with technological teaching in the school context. Artificial Intelligence (AI) is an area of research and development created from the need to expand the capacity of machines to solve problems and make decisions. We are experiencing the first generation of products that employ methods and techniques from the AI area. The most popular applications are observed in personal and financial assistants, robots, games, and georeferencing. In this scenario, a gap in teachers' knowledge of AI computing content is perceived, and it is necessary to offer teachers training to prepare them for the challenge of popularizing skills in schools in an interdisciplinary way, from the construction of computational experiences in STEAM (Science, Technology, Engineering, Arts and Mathematics) disciplines. The STEAM approach tends to be an opportunity to join forces with the National Curricular Base. When integrated, they can contribute to the construction of learning situations capable of providing relevant computational experiences to teaching in science and mathematics. As a guiding question, we propose the following: how to approach and develop complex knowledge related to Artificial Intelligence by promoting computational experiences in STEAM subjects? Considering the school context and aiming to elaborate and evaluate a teacher training, a Didactic Sequence was developed for teachers, incorporating knowledge about computational technologies, with PC skills and with the use of AI, aiming to contribute to the construction of teaching competencies, in order to enhance the quality of education in school with technological innovation. The didactic sequence and the experiments carried out allowed the construction of an educational product aimed at complementing teacher training, integrating concepts and practices supported by studies on Artificial Intelligence integrated into Teaching in the STEAM areas. The assessment and details are described in this document. [resumo fornecido pelo autor]
Graças a esforços científicos, a disseminação do pensamento computacional intensificou as inovações tecnológicas com uso de inteligência artificial, tornando-as imprescindíveis em nosso cotidiano. Embora presente no meio científico, o PC apenas recentemente revelou-se importante na Educação, portanto, nota-se uma preocupação emergente e significativa com o ensino tecnológico no contexto escolar. A Inteligência Artificial (IA) é uma área de pesquisa e desenvolvimento criada a partir da necessidade de ampliar a capacidade das máquinas em resolver problemas e tomar decisões. Experimenta-se a primeira geração de produtos que empregam métodos e técnicas oriundos da área da IA. As aplicações mais populares são observadas em assistentes pessoais e financeiros, robôs, jogos e no georreferenciamento. Nesse cenário, percebe-se uma lacuna no conhecimento docente em conteúdos de computação para IA, sendo necessário oferecer uma formação aos docentes para prepará-los para o desafio de popularizar nas escolas competências de forma interdisciplinar, a partir da construção de experiências computacionais nas disciplinas STEAM. A abordagem STEAM tende a ser uma oportunidade de unir forças com a Base Nacional Curricular. Quando integradas, elas podem contribuir com a construção de situações de aprendizagem capazes de proporcionar experiências computacionais relevantes ao ensino nas Ciências e na Matemática. Como questão orientadora, propõe-se a seguinte: como abordar e desenvolver conhecimentos complexos relacionados à Inteligência Artificial promovendo experiências computacionais nas disciplinas STEAM? Considerando o contexto escolar e com intuito de elaborar e avaliar uma formação docente, foi desenvolvida uma Sequência Didática para professores, incorporando conhecimentos sobre tecnologias computacionais, com as habilidades do PC e com uso da IA, visando contribuir com a construção de competências docentes, de modo a potencializar a qualidade do ensino na escola com inovação tecnológica. A sequência didática e os experimentos realizados permitiram a construção de um produto educacional destinado à complementação da formação docente, integrando conceitos e práticas apoiados em estudos sobre a Inteligência Artificial integrada ao Ensino das áreas STEAM. A avaliação e os detalhamentos são descritos neste documento. [resumo fornecido pelo autor]
Keywords: Inteligência artificial - Estudo e ensino; Tecnologia educacional; Professores - Formação; Artificial intelligence - Study and teaching; Educational technology; Teachers, Training of